Vytápění bytového domu - Ladomérská, Jana (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Ve své bakalářské práci zpracovávám návrh na vytápění a přípravu teplé vody v bytovém domě v Mostě. Jedná se o rekonstruovaný zděný dům se třemi podlažími. Ve výpočtové části se zabývám návrhem otopných ploch, rozvody otopné vody, přípravou teplé vody a zdroji tepla. Do objektu jsem navrhla otopná tělesa desková, trubková i podlahové konvektory. Rozvod teplovodní, dvoutrubkový, symetrický. Dům bude využívat centrální systém přípravy teplé vody. Zvolila jsem oddělenou přípravu otopné vody pro výrobu teplé užitové vody a otopné vody pro vytápění. V domě tedy budou instalovány dva kotle - kondenzační a nízkoteplotní. Kondenzační kotel bude sloužit pro přípravu otopné vody pro vytápění a nízkoteplotní pro přípravu teplé užitkové vody. v teoretické části se zaměřuji na problematiku regulace.

In my bachelor thesis I propose heating and the preparation of hot water in an apartment building in Most. It is a renovated brick house with free floors. In the calculation I deal with the design of heating surfaces, distribution of hot water, hot water preparation and the sources of heat. I designed panel and tubular radiators and floor convectors for the bulding. Hot water, two pipe and symmetric distribution. The house will use the central system of hot water preparation. I selected a separated preparation of hot water for the production of untility hot water and hot water for heating. There will be two boilers installed in the house - a condensing and a low-temperature one. The condensing boiler will serve to prepare hot water for heating and the low temperature boiler for the preparation of hot utility water. The theoretical part will focus on the issue of regulation.
Heating of Apartment Building
Keywords: vytápění; bytový dům; otopná tělesa; teplá voda; plynový kondenzační kotel; regulace; heating; apartment building; radiators; hot water; gas condensing boiler; regulation